Statistical Analysis on Student in Department of Mathematics (2007-2008) - Salim AL-Kutubi, Hadeel; Abd Yaseen, Faris (University of Thi-Qar Journal of Science, 2019)
This paper introduce statistical analysis on sample of mathematical student in college of science , Kufa university .A questionnaire was answered by all student in mathematics department . The aim was to investigate the desire of students to be mathematics teacher, go for higher study in one hand , and student opinions of their teachers from four variable namely , personality , scientific knowledge,ability of communication with students,the ability of evaluation ,using Excel program to draw graphs ,and factorial experiments to analyze data.